Lipocalin 10 as a New Prognostic Biomarker in Sepsis-Induced Myocardial Dysfunction and Mortality: A Pilot Study - Lu Wang; Wenjie Xie; Guang Li; Bo Hu; Wei Wu; Liying Zhan; Handong Zou (Mediators of Inflammation)
Introduction. Sepsis-induced myocardial dysfunction (SIMD) is the most common complications of sepsis and septic shock with extremely high incidence and mortality. Lipocalin 10 (Lcn10) has recently been identified as a potential biomarker for heart failure, yet its relation to sepsis has not been investigated. The purpose of this study was to explore whether circulating Lcn10 could be used as a prognostic tool in patients with SIMD. Methods. In this single-center observational pilot study, seventy-five sepsis patients were enrolled after sepsis diagnosis or ICU admission (45.3% female, median age 60 years), and 35 patients (46.7%) developed myocardial dysfunction. Serum Lcn10 levels of septic patients were measured using the enzyme-linked immunosorbent assay (ELISA) at the time of admission. Other biomarkers of cardiac function and Lcn10 concentration were compared between SIMD and non-SIMD groups. Results. We observed that the median Lcn10 levels were 2.780 ng/mL in patients with SIMD and 2.075 ng/mL in patients without SIMD (P<0.05). The area under the receiver operating characteristic (ROC) curve for the diagnosis of SIMD was 0.797 (P<0.05). In addition, elevated serum Lcn10 levels at the time of admission were positively associated with 28-day mortality in septic patients. Conclusions. Our study indicates that circulating Lcn10 levels may serve as a novel biomarker for the diagnosis and prognosis of myocardial dysfunction induced by sepsis. An additional large multicenter study may be warranted to confirm the findings of this study.